Methylene blue promotes quiescence of rat neural progenitor cells - Xie, Luokun; Choudhury, Gourav R.; Wang, Jixian; Park, Yong; Liu, Ran; Yuan, Fang; Zhang, Chun-Li; Yorio, Thomas; Jin, Kunlin; Yang, Shao-Hua (Frontiers in Cellular Neuroscience, 2014)
Neural stem cell-based treatment holds a new therapeutic opportunity for neurodegenerative disorders. Here, we investigated the effect of methylene blue on proliferation and differentiation of rat neural progenitor cells (NPCs) both in vitro and in vivo. We found that methylene blue inhibited proliferation and promoted quiescence of NPCs in vitro without affecting committed neuronal differentiation. Consistently, intracerebroventricular infusion of methylene blue significantly inhibited neural progenitor cell proliferation at the subventricular zone (SVZ). Methylene blue inhibited mTOR signaling along with down-regulation of cyclins in NPCs in vitro and in vivo. In summary, our study indicates that methylene blue may delay NPC senescence through enhancing NPCs quiescence.